FAKTOR RISIKO YANG BERHUBUNGAN DENGAN KAPASITAS VITAL PARU PADA PEKERJA BAGIAN PRODUKSI DI INDUSTRI BATU KAPUR - Febri Indra Pratama; Ari Suwondo; Bina Kurniawan (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2016)
Subdistrict Rowokele Kebumen has some informal sector industries engaged in the processing of limestone or commonly known as tobong. Chalk dust is a byproduct of the processing of limestone. Vital lung capacity (VLC) can decrease pollution caused by dust particles, one of which is the chalk dust. Based on the survey conducted in July 2013 found 70% of respondents experienced a subjective complaint of respiratory-related such as shortness of breath, breathing a little heavy, and shortness of breath. The purpose of this study was to analyze the risk factors associated with lung vital capacity on the part of workers in the industrial production of limestone (tobong). This research is a quantitative type of explanatory research and cross sectional approach. Sample selection technique with a total sampling totaling 34 workers. Examination of lung vital capacity on each respondent performed officials Medical Center Pulmonary Disease (BP4) Kebumen. The results showed that there is a relationship between age, length of employment, length of exposure, smoking and exercise habits with lung vital capacity and there is no relationship between the history of the disease, the use of PPE, and the nutritional status of the lung vital capacity. Based on the results of the calculation of prevalence ratio (PR), it is known that workers with tenure ≥ 10 years 2.67 times greater risk of decreased VLC compared with workers with tenure <10 years; workers with long exposure to ≥ 8 hours 1,538 times greater risk of decreased VLC compared to workers with long exposure < 8 hours; workers who have the smoking habit at 3.68 times greater risk of decreased VLC compared to workers who do not have the habit of smoking; workers who did not exercise regularly 4.3 times greater risk of decreased VLC compared with workers who regularly exercise.